Green organizational climate’s promotion of managers’ organizational citizenship behavior for the environment: Evidence from the Portuguese hospitality context - Henriques, I.; Mouro, C.; Duarte, A. P. (Sustainability, 2024)
Society at large has become increasingly concerned about climate change and sustainable development, so tourism and travel service providers have begun to focus more actively on sustainable development goals. Prior research has shown that supervisors’ support fosters employee green behavior and companies’ environmental performance. This study concentrated on Portuguese hospitality contexts to develop a fuller understanding of how organizations’ green efforts can combine with the individual variables highlighted by the theory of planned behavior (TPB) (i.e., attitudes, subjective norms, and perceived behavioral control) to encourage supervisors’ organizational citizenship behavior for the environment (OCBE). Data on 74 hotel managers were collected with an online survey. Multiple regression analysis revealed that perceived green organizational climate positively correlates with TPB variables, thereby increasing supervisors’ intention to adopt and encourage OCBE in their workplaces. These findings clarify how organizational and individual factors foster managers’ OCBE. The results have practical implications for organizations seeking to promote their managers’ pro-environmental behavior to boost their environmental sustainability.